2011
DOI: 10.1680/macr.9.00110
|View full text |Cite
|
Sign up to set email alerts
|

Geopolymer and Portland cement concretes in simulated fire

Abstract: High-strength Portland cement concrete has a high risk of spalling in fire. Geopolymer, an environmentally friendly alternative to Portland cement, is purported to possess superior fire-resistant properties. However, the spalling behaviour of geopolymer concrete in fire is unreported. In this paper, geopolymer and Portland cement concretes of strengths from 40 to 100 MPa were exposed to rapid temperature rises, simulating fire exposures. Two simulated fire tests, namely rapid surface temperature rise exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(70 citation statements)
references
References 23 publications
3
63
0
4
Order By: Relevance
“…In contrast to the composites based on Portland cement, alkali-activated slag shows a much better performance when exposed to very high temperatures. [7][8][9] Similar to the case of Portland cement, a partial dehydration and decomposition of the binder can be observed up to 600°C. The principle changes in the microstructure of alkali-activated slag occur between 600°C and 800°C, when the dehydration of the C-A-S-H phase is complete and new phases start to crystallize, among which akermanite is dominant.…”
Section: Introductionmentioning
confidence: 55%
“…In contrast to the composites based on Portland cement, alkali-activated slag shows a much better performance when exposed to very high temperatures. [7][8][9] Similar to the case of Portland cement, a partial dehydration and decomposition of the binder can be observed up to 600°C. The principle changes in the microstructure of alkali-activated slag occur between 600°C and 800°C, when the dehydration of the C-A-S-H phase is complete and new phases start to crystallize, among which akermanite is dominant.…”
Section: Introductionmentioning
confidence: 55%
“…The development of alkali-activated slag (AAS) cements has been object of intensive research recently [1]. The AAS cements are manufactured by mixing fine-ground glass slag with strong alkaline solutions, such as water glass NaOH and Na2CO3.…”
Section: Introductionmentioning
confidence: 99%
“…The mix design used in this research was based on the work reported by Zhao & Sanjayan [19] and is shown in Table 3. Aggregate weights shown in Table 3 are in the saturated surface dry condition.…”
Section: Designmentioning
confidence: 99%